2016
DOI: 10.5500/wjt.v6.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to increase intestinal length: Methods used for intestinal regeneration and bioengineering

Abstract: Inadequate absorptive surface area poses a great challenge to the patients suffering a variety of intestinal diseases causing short bowel syndrome. To date, these patients are managed with total parenteral nutrition or intestinal transplantation. However, these carry significant morbidity and mortality. Currently, by emergence of tissue engineering, anticipations to utilize an alternative method to increase the intestinal absorptive surface area are increasing. In this paper, we will review the improvements ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Although ileal loop vascularization has been preserved, the insufficient blood supply to the midportion of the graft could explain such a shrinkage extent. Other similar reports seem to confirm that a good vascular supply is critical for balanced growth of the neointestine especially at the earliest phase of ABS remodeling [17,22,40,41]. Strictures and important shrinkages were not found in ABS antimesenteric patches, probably because every part of the patch is close to the bowel's intact edges for its whole length and could take advantage of the good vascular supply of the surrounding intestine [24,25].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Although ileal loop vascularization has been preserved, the insufficient blood supply to the midportion of the graft could explain such a shrinkage extent. Other similar reports seem to confirm that a good vascular supply is critical for balanced growth of the neointestine especially at the earliest phase of ABS remodeling [17,22,40,41]. Strictures and important shrinkages were not found in ABS antimesenteric patches, probably because every part of the patch is close to the bowel's intact edges for its whole length and could take advantage of the good vascular supply of the surrounding intestine [24,25].…”
Section: Discussionmentioning
confidence: 68%
“…Recent advances in the field of tissue regeneration are offering promising therapeutic tools for the treatment of SBS [16,17]. Several reports have described animal models in which the feasibility and efficacy of acellular biologic scaffolds (ABSs) derived from extracellular matrixes of different tissues can promote the growth of neointestine that histologically resembles native intestine [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This small case series concluded that reestablishment of GI tract continuity after total enterectomy seems to be the best option for postoperative fluid and electrolyte management. Digestive tract restoration can facilitate electrolyte control and dietary support of the patient and can serve as a bridge to newer drug or surgical treatments [ 6 8 ], including small bowel transplantation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%